2017
DOI: 10.1099/ijsem.0.002035
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas wadenswilerensis sp. nov. and Pseudomonas reidholzensis sp. nov., two novel species within the Pseudomonas putida group isolated from forest soil

Abstract: Within the frame of a biotechnological screening, we isolated two Pseudomonas strains from forest soil. 16S rRNA gene sequence analysis indicated that strain CCOS 864T shared 99.8 % similarity with Pseudomonas donghuensis HYST, while strain CCOS 865T shared 99.0 % similarity with Pseudomonas putida DSM 291T and lower similarity with other P. putida group type strains. Based on multilocus sequence analysis, the two strains were genotypically distinct from each other, each forming a separate clade. Strains CCOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Investigation of the pan-genome revealed that P. wadenswilerensis CCOS 864 T has a complete gene set for p-HPA degradation ( Figure 3A), which was absent from the genome of P. reidholzensis CCOS 865 T . Positive growth of P. wadenswilerensis CCOS 864 T with this compound was obtained before [16], supporting our findings from the genomes. The hpaBC genes for degradation of p-HPA to homoprotocatechuic acid (HPC) and the hpaAG1G2EDF-nicT-hpaHIR gene cluster for the degradation from HPC to succinyl-CoA and acetyl-CoA by meta-cleavage [35,37] were found in the genome of P. wadenswilerensis CCOS 864 T .…”
Section: Degradation Of Aromatic Compoundssupporting
confidence: 89%
See 3 more Smart Citations
“…Investigation of the pan-genome revealed that P. wadenswilerensis CCOS 864 T has a complete gene set for p-HPA degradation ( Figure 3A), which was absent from the genome of P. reidholzensis CCOS 865 T . Positive growth of P. wadenswilerensis CCOS 864 T with this compound was obtained before [16], supporting our findings from the genomes. The hpaBC genes for degradation of p-HPA to homoprotocatechuic acid (HPC) and the hpaAG1G2EDF-nicT-hpaHIR gene cluster for the degradation from HPC to succinyl-CoA and acetyl-CoA by meta-cleavage [35,37] were found in the genome of P. wadenswilerensis CCOS 864 T .…”
Section: Degradation Of Aromatic Compoundssupporting
confidence: 89%
“…The presence of both p-HPA degradation gene clusters was confirmed for 15 of 43 members of the P. putida group (Figure 2). Comparative genomic results of this feature matched with the phenotypical results obtained before for strains that were tested in their studies [16,38]. In comparison to the cluster in P. wadenswilerensis CCOS 864 T , the cluster in P. entomophila L48 T differed by the absence of the putative metabolite transport protein nicT, while in Pseudomonas sp.…”
Section: Degradation Of Aromatic Compoundssupporting
confidence: 76%
See 2 more Smart Citations
“…On the basis of their 16S rDNA sequences, the strains harbouring the orthologous cluster are representatives of P. donghuensis (HYS, P482, Irchel 3F5, 1239, ABAC8, NBRC 111117 and RIT263), P. qingdaonensis (JJ3, BIGb0473, PA14H7, 1033, MF6396, BRM28 and UASWS0946) and P. wadenswilerensis (SNU WT1), being the three of them recently described species within the broad P. putida group (Gao et al, 2015;Frasson et al, 2017;Wang et al, 2019) (Fig. S1).…”
Section: Identification Of a Gene Cluster Involved In Fungal Antagonismmentioning
confidence: 99%